Osmundea sanctarum sp. nov. (Ceramiales, Rhodophyta) from the southwestern Atlantic Ocean - Rocha-Jorge, Renato; Cassano, Valéria; Barros-Barreto, Maria Beatriz; Díaz-Larrea, Jhoana; Sentíes, Abel; Gil-Rodríguez, Maria Candelaria; Fujii, Mutue Toyota (Phytotaxa, 2013)
An ongoing phycological survey in the Laje de Santos Marine State Park (LSMSP) of São Paulo in southeastern Brazil revealed a previously undescribed species of Osmundea (Rhodophyta, Rhodomelaceae), which was found in the subtidal zone at a depth of 7 to 20 m. Morphological studies conducted on Osmundea specimens collected in the LSMSP revealed characteristics typical of the genus Osmundea, including two pericentral cells per each axial segment and tetrasporangia cut off randomly from cortical cells. The phylogenetic position of this species was inferred by analysis of chloroplast-encoded rbcL gene sequences from 37 taxa, including one Rhodomelaceae and one Ceramiaceae as outgroups. The Brazilian species of Osmundea formed a well-supported clade with the ‘Spectabilis’ group from the coast of Pacific North America, composed of O. spectabilis, O. blinksii, O. splendens and O. sinicola. The present species, however, diverged greatly from the ‘Spectabilis’ group representatives (5.4–7.1%), which confirms that it constitutes a different taxonomic entity, herein proposed as the new species Osmundea sanctarum M.T. Fujii & Rocha-Jorge. This is the first report of a member of Osmundea related to the ‘Spectabilis’ group in the South Atlantic Ocean.